Business sustainability practices and financial performance in the creative economy sector in Indonesia: Moderating role of power distance and long-term orientation - Mohammad Herli; Bambang Tjahjadi; Hamidah Hamidah (Intangible Capital)
Purpose: This research explores the effect of business sustainability practices (BSP) on micro, small, and medium enterprises (MSMEs) financial performance, with cultural dimensions serving as moderating variables.